PROACTIVE APPROACH TO SMART MAINTENANCE AND LOGISTICS AS A AUXILIARY AND SERVICE PROCESSES IN A COMPANY - Rakyta, Miroslav; Fusko, Miroslav; Hercko, Jozef; Závodská, Ľudmila; Zrnić, Nenad (Journal of Applied Engineering Science, 2016)
The article describes a proactive approach to smart maintenance and smart logistics. It presents the areas through which all companies must pass. For its successful implementation it is necessary to introduce appropriate management practices also into the area of maintenance. Irrespective of the level of maintenance work in a particular organization, gradual development of maintenance management is needed. The goal is excellent quality of equipment maintenance. The logistics of tomorrow will be supported, to a high extent, by logistics assistance systems. The logistics world is changing – key terms such as Smart Logistics, digitization of the supply chain or Industry 4.0 are widely discussed and already mega trends.